The first count of Gondomar's library and diplomatic practice (1613-1622) - Oyarbide Magana, EE (2019)
This thesis offers the first detailed study on the intersection between diplomacy and Spanish libraries during the early modern period. It focuses on the library of Diego Sarmiento de Acuña, first count of Gondomar (1567-1626). Once deemed by John Elliott as the ‘greatest specialist in English affairs’ of Spain, Gondomar oversaw a very notable embassy in London from 1613 to 1622. He also became one of the main conduits of English information to Madrid during the Anglo-Spanish peace of the early 17th century (1604-1625).